Effect of Capsules Containing Waste Mineral Oil on Mechanical Properties of Hot Mix Asphalt - Sarışın, Esma; Yilmaz, Mehmet; Yalçın, Erkut (Hüseyin AKBULUT, 2022)
Nowadays, the importance of hot bituminous mixtures in terms of transportation is quite high. Bituminous hot mixes become brittle with the increase in stiffness due to the increasing traffic load and climatic conditions over time. This situation causes cracks and deterioration in the pavement. Therefore, it is necessary to observe the bituminous mixture layers regularly, and to carry out maintenance and repair activities. However, this may not always be possible for economic or technical reasons. For this reason, the idea of self-healing hot mix with bitumen has gained importance in recent years. Within the scope of the study, waste mineral oil, which is released after the maintenance of the vehicles, was used as a reparative material in the capsules. Capsules providing optimum conditions have been produced. Capsules were added to the mixtures in four different ratios (0.25%, 0.50%, 0.75% and 1.00% by weight of aggregate). Four different cures were applied to the bituminous hot mixtures. Three-point bending fatigue test was applied to BSK samples. In addition, the effect of capsule addition on the mechanical properties of the mixtures was evaluated.

Günümüzde ulaşım açısından bitümlü sıcak karışımların önemi oldukça fazladır. Bitümlü sıcak karışımlar zamanla artan trafik yükü ve iklim koşullarına bağlı olarak rijitliğin artmasıyla kırılgan hale gelmektedir. Bu durum üst yapıda çatlaklara ve bozulmalara neden olmaktadır. Bu nedenle bitümlü karışım tabakalarının düzenli olarak gözlenmesi, bakım ve onarım faaliyetlerinin gerçekleştirilmesi gerekmektedir. Ancak ekonomik veya teknik nedenlerden ötürü bu her zaman mümkün olmayabilir. Bu nedenle kendini onarabilen bitümlü sıcak karışım fikri son yıllarda önem kazanmıştır. Çalışma kapsamında kapsüllerde onarıcı malzeme olarak araçların bakımları sonrası açığa çıkan atık madeni yağ kullanılmıştır. Optimum şartları sağlayan kapsüller üretilmiştir. Kapsüller, karışımlara dört farklı oranda (agrega ağırlığınca %0,25, %0,50, %0,75 ve %1,00) ilave edilmiştir. BSK numunelerine üç noktalı eğilme yorulma deneyi uygulanmıştır. Ayrıca kapsül ilavesinin karışımların mekanik özellikleri üzerindeki etkisini değerlendirilmiştir.
Atık Madeni Yağ İçeren Kapsüllerin Bitümlü Sıcak Karışımların Mekanik Özelliklerine Etkisi
Keywords: Civil Engineering; İnşaat Mühendisliği